Lateral cavo-caval shunt: an alternative veno-venous bypass in liver surgery - Rayar, Michel; Levi Sandri, Giovanni Battista; Blondeau, Marc; Lakehal, Mohamed; Desfourneaux, Véronique; Sulpice, Laurent; Meunier, Bernard; Boudjema, Karim (Translational Gastroenterology and Hepatology; Vol 3 (May 2018): Translational Gastroenterology and Hepatology, 2018)
When inferior vena cava (IVC) resection is mandatory during liver surgery, use of a veno-venous bypass (VVB) is usually required despite its specific related adverse events. We describe a safe and alternative technique which allows both derivation of the portal and the caval blood flow by performing a lateral cavo-caval shunt using a prosthetic graft.